Bilateral Changes of Spontaneous Activity Within the Central Auditory Pathway Upon Chronic Unilateral Intracochlear Electrical Stimulation. Issue 10 (December 2015) - Basta, Dietmar; Götze, Romy; Gröschel, Moritz; Jansen, Sebastian; Janke, Oliver; Tzschentke, Barbara; Boyle, Patrick; Ernst, Arne
Abstract : Objectives: In recent years, cochlear implants have been applied successfully for the treatment of unilateral hearing loss with quite surprising benefit. One reason for this successful treatment, including the relief from tinnitus, could be the normalization of spontaneous activity in the central auditory pathway because of the electrical stimulation. The present study, therefore, investigated at a cellular level, the effect of a unilateral chronic intracochlear stimulation on key structures of the central auditory pathway. Design: Normal-hearing guinea pigs were mechanically single-sided deafened through a standard HiFocus1j electrode array (on a HiRes 90k cochlear implant) being inserted into the first turn of the cochlea. Four to five electrode contacts could be used for the stimulation. Six weeks after surgery, the speech processor (Auria) was fitted, based on tNRI values and mounted on the animal's back. The two experimental groups were stimulated 16 hours per day for 90 days, using a HiRes strategy based on different stimulation rates (low rate (275 pps/ch), high rate (5000 pps/ch)). The results were compared with those of unilateral deafened controls (implanted but not stimulated), as well as between the treatment groups. All animals experienced a standardized free field auditory environment. Results: The low-rate group showed a significantly lower average spontaneous activity bilaterally in the dorsal cochlear nucleus and the medial geniculate body than the controls. However, there was no difference in the inferior colliculus and the primary auditory cortex. Spontaneous activity of the high-rate group was also reduced bilaterally in the dorsal cochlear nucleus and in the primary auditory cortex. No differences could be observed between the high-rate group and the controls in the contra-lateral inferior colliculus and medial geniculate body. The high-rate group showed bilaterally a higher activity in the CN and the MGB compared with the low-rate group, whereas in the IC and in the AC a trend for an opposite effect could be determined. Conclusions: Unilateral intracochlear electrical stimulation seems to facilitate the homeostasis of the network activity, since it decreases the spontaneous activity that is usually elevated upon deafferentiation. The electrical stimulation per se seems to be responsible for the bilateral changes described above, rather than the particular nature of the electrical stimulation (e.g., rate). The normalization effects of electrical stimulation found in the present study are of particular importance in cochlear implant recipients with single-sided deafness.